Clinical periodontology and implant dentistry - Lindhe, Jan (Munksgaard, 1998)
The third edition of the \"Textbook of Clinical Periodontology\". Most chapters from the previous edition have been entirely rewritten due to the immense biologic and technologic advances in periodontics in recent years. This text covers all aspects of periodontics. The aetiology of the various diseases in the periodontium and the pathogenic mechanisms by which the periodontium may be destroyed are described, and the various treatment modalities are presented with due acknowledgement of their scientific background and the experimental evidence for the outcome of the treatment. The presentation of clinical procedures is accompanied by step-by-step colour photographs or illustrative schematic drawings. The new chapters cover topics such as the use of antiseptics and antibiotics in periodontal therapy, aesthetics in peridontal therapy and the various aspects of implant treatment.
Keywords: zubní implantáty; Periodontics; ortodoncie; Dental Implants; zubní lékařství; parodontologie